Naegleria fowleri: Swimming with Death as the Major Outbreak in Pakistan - Muhammad NAVEED; Zeshan ALI; Masooma KHWAR; Wahab NAZIR; Nauman KHALID (Tehran University of Medical Sciences, 2019)
Naegleria fowleri: Swimming with Death as the Major Outbreak in Pakistan